Michael Ondaate’s The English Patient (1992): The Question of Identity - Al-Janabi, Hazem Kamel Abd; Az-Zubaidy, Thamir R. S. (Journal of Ecohumanism, 2024)
The main objective of the present paper is to demonstrate the extent to which the question of identity is key to contemporary concerns, particularly in the context of the postcolonial novel. With this in mind, I argue that Michael Ondaatje’s novel entitled the English Patient (1992) offers articulations of identity that dismantle conventional notions of fixity and rigidity and that reinterpret identity as porous, fluid, hybrid, and complex formations that are irreducible to one single homogenous strand. The emphasis on the complexity that is intrinsic to identity-formation is crucial to fostering greater awareness of colonial and imperial discourses, giving rise to other voices in the knowledge-making processes, hence criticak illumination. The paper, therefore, is a contribution to postcolonial studies, particularly in relation to identity as a concept.